Prevalence of Colistin-Resistant Klebsiella Pneumoniae Isolates in Turkey Over a 20-Year Period: a Systematic Review and Meta-Analysis - Kahraman Kilbas, E.P.; Kilbas, I.; Ciftci, I.H.; Kilbas, Elmas Pinar Kahraman (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Klebsiella pneumoniae is one of the leading causes of healthcare-associated infections and poses challenges in its treatment owing to its high antibiotic resistance. The development of resistance to colistin, which is used as a last resort, has become a major public health problem worldwide. This study was planned according to the PRISMA guidelines and included studies reporting the prevalence of colistin-resistant K. pneumoniae in Turkey between 2004 and 2024 through a systematic literature review. A total of 28 original research articles were included in the meta-analysis. Data were analyzed using the SPSS and CMA software. The pooled colistin resistance of a total of 8916 K. pneumoniae strains from 28 studies included in this meta-analysis was found to be 1.63% (95% CI: 1.51–3.12). Colistin resistance increased significantly over time. A higher resistance rate was detected in the strains tested using the EUCAST guidelines and broth microdilution method. The year of the study and validation methods contributed to the heterogeneity observed in the studies. This meta-analysis reveals that colistin-resistant K. pneumoniae strains have increased over time in Turkey. Current data show that colistin resistance is not only a laboratory finding but has become a crisis, requiring urgent action in terms of hospital infection management and patient safety. Regional and global measures should be taken to ensure the appropriate use of antibiotics to control the development of resistance. © 2025 by the authors.
Keywords: Epidemiology; Gram-Negative Bacteria; Healthcare-Associated Infections; Multidrug Resistance